Techno-economic Analysis of Non-linear DG Penetration in Radial Distribution Systems - Kumar, Narinder; Kumar, Ashwani (Distributed Generation & Alternative Energy Journal, 2017)
Increasing penetration of Distributed Generation (DG) in recent years has presented new challenges for planning and optimal operation of integrated distribution systems. In this scenario, harmonic distortions caused by non-linear DG operation in the distribution networks have further added to the complexities of regulating such interconnected systems. In this article, a comprehensive analysis of unbalanced radial distribution systems (RDS) integrated with non-linear DG has been at - tempted. The analytical assessment has been carried out by considering various voltage harmonics in non-linear DG in the presence of shunt ca- pacitors in the radial distribution systems. Results are obtained for Total Harmonic Distortion (THD) of voltage and current at various buses of the RDS, along with harmonic power profile. An economic assessment of annual energy loss in the presence of non-linear DG has also been at- tempted. The proposed method is tested on two IEEE radial distribution feeders interconnected with non-linear DG. Results show that the pres- ence of even acceptable level of voltage harmonics in non-linear DG can cause severe harmonic amplification in the entire network, consequently leading to increased energy losses for certain harmonic orders.